2014
DOI: 10.3233/jad-131334
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Lumbar Puncture in the Study of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease: A Multicenter Study in Spain

Abstract: LP can be safely performed to study CSF biomarkers. The main complication is headache, associated with younger age and use of cutting-edge needles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 25 publications
3
70
2
Order By: Relevance
“…Less blood was used for EBP in OUH (median [minimum-maximum], 15 [7][8][9][10][11][12][13][14][15][16][17][18][19][20] mL) than in KUH (18 [15][16][17][18][19][20] mL) and in SCH (19 [18][19][20] mL; P = .014). The time from LP to EBP (P = .7), amount of blood used in EBP (P = .6), or duration of bed rest after EBP (P = .1) had no correlation with EBP efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Less blood was used for EBP in OUH (median [minimum-maximum], 15 [7][8][9][10][11][12][13][14][15][16][17][18][19][20] mL) than in KUH (18 [15][16][17][18][19][20] mL) and in SCH (19 [18][19][20] mL; P = .014). The time from LP to EBP (P = .7), amount of blood used in EBP (P = .6), or duration of bed rest after EBP (P = .1) had no correlation with EBP efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…This is a common problem in clinical research, particularly in psychiatry, as well as acupuncture [63]. In future research, a multicenter study [64][65][66][67] seems to be an interesting alternative not only to increase the sample size but also to exclude effects of practitioner bias and the experimental/clinical atmosphere [66].…”
Section: Sleep Variable After Acupuncture After Waitlistmentioning
confidence: 99%
“…We excluded studies that used pain as an inclusion or exclusion criterion, studies on induced pain (e.g. [13]), case reports or case series. Authors were contacted when studies reported one or more dementia subtypes, but did not display the results of the subtypes separately.…”
Section: Methodsmentioning
confidence: 99%